2020
DOI: 10.1038/s41598-020-58031-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower Systolic Blood Pressure in Normotensive Subjects is Related to Better Autonomic Recovery Following Exercise

Abstract: Blood pressure (Bp) is a cardiovascular parameter applied to detect cardiovascular risk. Recently, the pre-hypertension state has received greater consideration for prevention strategies. We evaluated autonomic and cardiorespiratory recovery following aerobic exercise in normotensive individuals with different systolic BP (SBP) values. We investigated 30 healthy men aged 18 to 30 years divided into groups according to systolic BP (SBP): G1 (n = 16), resting SBP <110 mmHg and G2 (n = 14), resting SBP between 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Thus, HR variability (HRV) is considered a practical way of assessing ANS in many situations. HRV evaluates the oscillations between inter-beat cardiac intervals (IBI) and scrutinizes the control of the ANS over heart rhythm (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HR variability (HRV) is considered a practical way of assessing ANS in many situations. HRV evaluates the oscillations between inter-beat cardiac intervals (IBI) and scrutinizes the control of the ANS over heart rhythm (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…It could be caused by changes of blood volume, cardiac output and decreased total peripheral resistance ( Joyner and Limberg, 2014 ). Additionally, de Oliveira et al (2020) showed that lower resting SBP is related to better autonomic recovery what is important during intense training and/or competitive session. Therefore, further analyses of the physiological (and psychological) response of the body induced by a single training session and competition are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HRV has been proposed as a monitoring/predicting tool for estimating the level of athletic performance ( Plews et al, 2013 ). Recently, a predictive role of HRV in pre-hypertensive patients has been suggested ( de Oliveira et al, 2020 ). Furthermore, a huge body of literature has been published proving the role of HRV as an independent predictor for cardiovascular disease and sudden cardiac death ( Thayer et al, 2010 ; Huikuri and Stein, 2013 ; Sessa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%